MENINGKATKAN AKTIVITAS BELAJAR DAN KETERAMPILAN KOMUNIKASI MENGGUNAKAN MODEL PANDIR - Muhamad Hasby Munawar; Ahmad Suriansyah; Ratna Purwanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The main problem discussed in this study is the lack of learning activities and communication skills for class V children at SDN Alalak Selatan 2. This research aims to describe the increase in teacher activity, learning activities and student communication skills. This is because learning tends to be one-way, Indonesian language learning emphasizes grammar, and learning does not use a variety of models. The method used in this research was Classroom Action Research which was carried out in 4 meetings. The data used is qualitative data obtained by observing teacher activities, student learning activities, and student communication skills. The results obtained were that teacher activity from meetings 1 to 4 increased from 83% to 98%. Student learning activity at the same meeting increased from 41% to 91%, while student communication skills increased from 41% to 86%. Completeness of student learning outcomes also increased from 41% to 100%. Based on these results, conclusions can be drawn that show the PANDIR model is effective in increasing teacher activity, learning activities, communication skills, and student learning outcomes.